Case Report: Laser speckle flowgraphy in a patient with uveitis due to immune-related adverse events by immune checkpoint inhibitors - Satoru Kase; Yui Yamashita; Satoshi Takeuchi; Susumu Ishida (Frontiers in Oncology)
PurposeIt remains unknown whether choroidal circulation could be altered at the onset of immune checkpoint inhibitor (ICI) uveitis compared with that before ICI treatment. Herein we report a patient with Vogt-Koyanagi-Harada (VKH) disease-like uveitis in the unaffected eye as an immune-related adverse effect (irAE) due to ICIs for metastatic choroidal melanoma who had received enucleation. Moreover, choroidal circulation and choroidal thickness were measured before and after treatment.MethodsA 58-year-old man had a medical history of enucleation in his left eye due to choroidal melanoma 6 years ago. Metastatic lesions in the gastrointestinal tracts and lung were found, and then he received ICIs three times. About 1 month later, he suffered from blurred vision and metamorphopsia in his right eye. Choroidal circulation was evaluated by mean blur rate (MBR), a relative value showing choroidal blood velocity on laser speckle flowgraphy. Central choroidal thickness (CCT) was measured on optical coherence tomography.ResultsSince ophthalmic findings revealed VKH-like uveitis, oral prednisolone of 30 mg was given for 2 weeks, which were then tapered. MBR was reduced and CCT increased at the onset of ICI uveitis compared with its baseline and resolution after corticosteroid treatment.ConclusionsChoroidal circulation was disrupted, possibly due to ICI-induced autoinflammatory reaction to the choroid, which was managed by corticosteroid treatment. The combination of MBR and CCT could be a useful biomarker for managing the patients with VKH-like uveitis by ICIs.